2022
DOI: 10.1021/acsmeasuresciau.2c00023
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Diagnostic Wound Dressings for Diabetic Wounds

Abstract: Chronic lower extremity wounds (diabetic foot ulcers) are a serious and prevalent complication of diabetes. These wounds exhibit low healing rates and present a high risk of amputation. Current diagnostic options for foot ulcers are limited to macroscopic wound analysis such as wound depth, implicated tissues, and infection. Molecular diagnostics promises to improve foot ulcer diagnosis, staging, and assessment of the treatment response. In this perspective, we report recent progress in understanding the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Ideally, diagnostic bandages sense these biomarkers in situ and provide prognostic information to the clinician at the point-of-care. Biomarkers of interest include markers of inflammation, oxidative stress, MMP activity, bacterial infection, and mechanical stress . Such molecular fingerprinting will also enable evidence-based treatment selection once molecular therapeutics become available for chronic wounds.…”
Section: Chronic Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, diagnostic bandages sense these biomarkers in situ and provide prognostic information to the clinician at the point-of-care. Biomarkers of interest include markers of inflammation, oxidative stress, MMP activity, bacterial infection, and mechanical stress . Such molecular fingerprinting will also enable evidence-based treatment selection once molecular therapeutics become available for chronic wounds.…”
Section: Chronic Woundsmentioning
confidence: 99%
“…Biomarkers of interest include markers of inflammation, oxidative stress, MMP activity, bacterial infection, and mechanical stress. 34 Such molecular fingerprinting will also enable evidence-based treatment selection once molecular therapeutics become available for chronic wounds. Diagnostic wound dressings therefore promise to pave the way for personalized medicine in chronic wounds.…”
mentioning
confidence: 99%
“…This Virtual Issue also focuses on translation, the process of exploring the therapeutic potential of drug candidates in relevant in vivo systems. , Chang and co-workers contributed three translational studies on investigational matrix metalloprotease (MMP) treatments for diabetic wounds. Lower extremity wounds are one of the most serious and prevalent complications of diabetes, with a lifetime incidence of 15–25% among patients with diabetes, and associated with low healing and high amputation rates. , MMP-9 recently emerged as a high-impact target to improve diabetic wound healing. Chang and co-workers showed that a low-molecular-weight MMP-9 inhibitor accelerated wound healing in infected diabetic mouse wounds alone and in combination with an antibiotic . In their efforts to translate this treatment, they also provided in vitro metabolism data in different species to select appropriate models for toxicology studies .…”
Section: Pharmacology and Safety Of Approved Diabetes Drugsmentioning
confidence: 99%
“…For instance, the stimuli-triggered degradation of the membrane was leveraged for diagnostic systems. Phospholipase-producing bacteria in wounds were detected by fluorescent cargo release after enzymatic degradation of the liposomal membrane. , Moreover, polymeric vesicles with analyte-sensitive pores have been employed to sense the pH or redox environment of a solution where the pore opens and allows a fluorogenic reaction to occur . Recent studies pointed to the potential of exploiting selectively permeable membrane properties to separate analytes from undesired interferences or provide a dedicated reaction compartment for chemical or enzymatic reactions to occur. Vesicles for diagnostic applications were mainly prepared by film rehydration, ,,,, but emulsification and ethanol injection were also used.…”
Section: Introductionmentioning
confidence: 99%